1988
DOI: 10.1111/j.1440-1754.1988.tb01364.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A status of children with a history of respiratory syncytial virus infection in infancy

Abstract: In order to extend our earlier observation that children who experience frequent respiratory episodes may benefit from Vitamin A supplementation, 206 children aged 2-7 years who had been hospitalized for bronchiolitis during infancy were randomized into a controlled trial of Vitamin A supplementation. Of these, 149 met the criteria of protocol compliance after 12 months of follow-up. Mean plasma retinol at baseline was 39.2 pgl100 ml (s.e.m. = 1.0) and did not increase after 12 months (mean = 36.0 pg/lOO ml, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…These data suggested that vitamin A might be a useful adjunctive therapy [94,109]. However, in a subsequent study oral administration of vitamin A did not decrease respiratory morbidity in children with acute RSV bronchiolitis [102].…”
Section: Other Therapiesmentioning
confidence: 95%
“…These data suggested that vitamin A might be a useful adjunctive therapy [94,109]. However, in a subsequent study oral administration of vitamin A did not decrease respiratory morbidity in children with acute RSV bronchiolitis [102].…”
Section: Other Therapiesmentioning
confidence: 95%
“…In fact, some of the hospital-based studies suggest an apparent increase in indicators of severity associated with vitamin A supplementation (41,85,105,146). A number of community-based trials have also found an apparent increase in respiratory symptoms in relation to vitamin A supplementation (34,39,103,104,112,136,144), particularly among children who are not undernourished. It is not clear whether this apparent increase in respiratory symptoms may be due to a proinflammatory immune response associated with the supplements.…”
Section: Vitamin a Supplementation And Clinical Outcomesmentioning
confidence: 96%
“…The various studies on the association between vitamin A deficiency and morbidity have not had very consistent results [17][18][19][20][21][22][23][24][25][26]. This may be explained by the fact that morbidity studies are hard to carry out.…”
Section: Vitamin a Deficiency And Morbiditymentioning
confidence: 97%